Betets avkastning på olika typer av naturbetesmark : en fält- och metodstudie - Back, Josefin (SLU/Dept. of Animal Nutrition and Management (until 231231), 2011)
Abstract A prerequisite to be able to use semi-natural pastures in an optimal way is knowledge about their conditions and properties. One thing to consider is the amount of herbage mass that can be produced during one season on different types of semi-natural pastures. That knowledge makes it easier to choose which type of animals and how many you are able to have in each paddock to maintain a high biodiversity and achieve the desired production of the animals at the same time.